Numerical model of heat transfer in skin lesions - Ziemowit Ostrowski; Piotr Buliński; Wojciech Adamczyk; Paweł Kozołub; Andrzej J. Nowak (Advances in Mechanical and Materials Engineering, 2015)
Preliminary results of numerical modelling of skin undergoing thermal stimulation (mild cooling) in a human forearm is presented. Small brass compress was used for cooling purposes. The skin recovery process was then analysed. Temperature history for N = 14 samples was recorded using IR camera. The samples come from 8 male adults (age 25-38 years). A numerical model of heat transfer in tissues and CFD model of surrounding air (natural convection) was proposed. Simulation results were validated against experimental data.